2000
DOI: 10.1002/1096-9071(200010)62:2<267::aid-jmv20>3.3.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Type 1‐like immune response is found in children with respiratory syncytial virus infection regardless of clinical severity

A.H. Brandenburg,
A. Kleinjan,
B. van het Land
et al.

Abstract: The immunological response of infants younger than six months to infection with respiratory syncytial virus (RSV) was studied in relation to clinical severity. IL-6 and IL-8 were found more frequently and at higher levels in the plasma samples of more severely ill patients and no significant differences were found in the levels of cytokines differentiating between Type 1 and Type 2 responses. Cellular infiltrates in nasopharyngeal washings consisted mainly of polymorphonuclear granulocytes and monocytes. Eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…We understand that one of the problems in examining inflammatory cytokines in serum is that these measurements may not reflect accurately the response in airways. However, the immunological responses have previously been studied in serum and plasma in children with respiratory infection with RSV (9,14) and a recent study reported that IFN-c was undetectable in nasopharyngeal secretions (27). Therefore in this study, we aimed to investigate the agerelated immunological responses during naturally occurring RSV bronchiolitis by measuring the serum concentrations of Th1 and Th2 cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We understand that one of the problems in examining inflammatory cytokines in serum is that these measurements may not reflect accurately the response in airways. However, the immunological responses have previously been studied in serum and plasma in children with respiratory infection with RSV (9,14) and a recent study reported that IFN-c was undetectable in nasopharyngeal secretions (27). Therefore in this study, we aimed to investigate the agerelated immunological responses during naturally occurring RSV bronchiolitis by measuring the serum concentrations of Th1 and Th2 cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many components of the immune system are activated during acute RSV infection (7)(8)(9)(10). Although the critical components contributing to severe forms of bronchiolitis have not been identified, there have been many studies discussing the associations of Th1 or Th2 cytokine responses with disease severity (11)(12)(13)(14)(15)(16). However, it has not been reported if there is any age-related difference in cytokine response to RSV infection in relation to the developmental change of immune response during early life, which may explain the more There have been longitudinal studies of the developmental change of the immune system during the first year of life.…”
mentioning
confidence: 99%
“…Whether there is an association of any pattern of pro-inflammatory cytokine responses with AB or wheezing in infancy is unclear. 12,[24][25][26][27] IL-11, a cytokine that may be involved in airways hyperresponsiveness due to viral infections, 28 was only detected in a small number of patients (15%), making further comment on the role of this cytokine difficult.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, there have been only two other studies involving the cytokine response patterns in human RSV infection using ow cytometry, with con icting results (18,19). Using whole blood culture and cytokine induction by short-term activation with PMA and ionomycin, Bendelja et al (18) found a predominantly type 2 response in infants who had increased IL-4 expression and decreased IFN-g expression in CD4 ‡ and CD8 ‡ lymphocytes.…”
Section: Discussionmentioning
confidence: 99%